PENGARUH KUALITAS PRODUK, SUASANA TEMPAT DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA RUMAH MAKAN ASIH JAYA BABAT - Nawari Nawari; Siska Dwi Setyawati (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2019)
Nowadays the competition in the culinary world is growing rapidly, especially restaurants or restaurants, this phenomenon has only recently been booming, now we easily find everywhere, both large restaurants and simple houses (warungs). Therefore marketing is very important to support the success of a business. The purpose of this study is to find out the quality of the product, the atmosphere of the place and the quality of service to the purchasing decision at the Asih Jaya Babat restaurant. The method in this study is quantitative by distributing questionnaires to 67 respondents. The analytical method used is multiple linear regression, classical assumption test, partial t test and simultaneous f test. The results of this study indicate that the quality of products has a significant positive effect on purchasing decisions, the atmosphere of the place has a positive and significant effect, and the quality of service has a negative effect on purchasing decisions at the Asih Jaya Babat restaurant.